"Ja tak i ne obžila druguju čast` seba - svoe telo": telesnost` v tvorčestve Mariny Cvetaevoj = "I still have not grown roots in another part of myself - my body...": the corporeality in the work of Marina Tsvetaeva - Janczuk, Elena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the picture of human corporeality of the poetry of Marina Tsvetaeva the human chest takes the special place and it concerns to a different aspects. First and foremost, should be defined the external qualities of it. Second , it is perceived as a place in which is placed the heart (or soul), which produces the breath, and most importantly - the sound (voice), and these functions of chest are the most important for a poet.
Keywords: Cwietajewa, Marina Iwanowna (1892-1941); ciało; serce; głos; cielesność; pierś; oddech; metafizyka; body; voice; heart; corporeality; breath; metaphysics